Targeted SNP discovery in Atlantic salmon ( Salmo salar ) genes using a 3'UTR-primed SNP detection approach - Høyheim Bjørn; Lunner Sigbjørn; Andreassen Rune (BMC Genomics, 2010)
Abstract Background Single nucleotide polymorphisms (SNPs) represent the most widespread type of DNA variation in vertebrates and may be used as genetic markers for a range of applications. This has led to an increased interest in identification of SNP markers in non-model species and farmed animals. The in silico SNP mining method used for discovery of most known SNPs in Atlantic salmon ( Salmo salar ) has applied a global (genome-wide) approach. In this study we present a targeted 3'UTR-primed SNP discovery strategy that utilizes sequence data from Salmo salar full length sequenced cDNAs (FLIcs). We compare the efficiency of this new strategy to the in silico SNP mining method when using both methods for targeted SNP discovery. Results The SNP discovery efficiency of the two methods was tested in a set of FLIc target genes. The 3'UTR-primed SNP discovery method detected novel SNPs in 35% of the target genes while the in silico SNP mining method detected novel SNPs in 15% of the target genes. Furthermore, the 3'UTR-primed SNP discovery strategy was the less labor intensive one and revealed a higher success rate than the in silico SNP mining method in the initial amplification step. When testing the methods we discovered 112 novel bi-allelic polymorphisms (type I markers) in 88 salmon genes [dbSNP: ss179319972-179320081, ss250608647-250608648], and three of the SNPs discovered were missense substitutions. Conclusions Full length insert cDNAs (FLIcs) are important genomic resources that have been developed in many farmed animals. The 3'UTR-primed SNP discovery strategy successfully utilized FLIc data to detect novel SNPs in the partially tetraploid Atlantic salmon. This strategy may therefore be useful for targeted SNP discovery in several species, and particularly useful in species that, like salmonids, have duplicated genomes.